Up and Down﻿ with Technology. - STEWART, JENNY (Quadrant Magazine, 2016)
The article offers the author's insights on technological advancement. Topics discussed include information from social networking service Google, computer-based intelligence and programming, and advantages of technology in completing a task. He also mentioned medical technology, information systems, and disadvantages of technology.